2013
DOI: 10.1007/s10745-013-9572-1
|View full text |Cite
|
Sign up to set email alerts
|

Urban Forest Justice and the Rights to Wild Foods, Medicines, and Materials in the City

Abstract: Urban forests are multifunctional socio-ecological landscapes, yet some of their social benefits remain poorly understood. This paper draws on ethnographic evidence from Seattle, Washington to demonstrate that urban forests contain nontimber forest products that contribute a variety of wild foods, medicines, and materials for the wellbeing of urban residents. We show that gathering wild plants and fungi in urban forests is a persistent subsistence and livelihood practice that provides sociocultural and materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(171 citation statements)
references
References 54 publications
(49 reference statements)
5
143
0
14
Order By: Relevance
“…The plants or plant parts that these studies show are commonly collected have a wide range of uses, including: berries or fruit for home consumption or sale; leaves, roots, and bark for medicines; poles for construction; and reeds for craft. However, in the developed world, urban foraging can also be a means towards improved food security, and supply other material and immaterial benefits [12]. For example, work in Seattle in the US has shown that far from being unimportant, harvesting in urban green areas is practiced by many and for multiple reasons [11], such as the collection of fruit and greens for food, medicinal products, and raw materials for craft work.…”
Section: Emerging Themes Of Urban Foragingmentioning
confidence: 99%
“…The plants or plant parts that these studies show are commonly collected have a wide range of uses, including: berries or fruit for home consumption or sale; leaves, roots, and bark for medicines; poles for construction; and reeds for craft. However, in the developed world, urban foraging can also be a means towards improved food security, and supply other material and immaterial benefits [12]. For example, work in Seattle in the US has shown that far from being unimportant, harvesting in urban green areas is practiced by many and for multiple reasons [11], such as the collection of fruit and greens for food, medicinal products, and raw materials for craft work.…”
Section: Emerging Themes Of Urban Foragingmentioning
confidence: 99%
“…These "forageables" include wild and domesticated species that occur spontaneously, those that spread or persist without human intervention and those that are introduced primarily for non-edible/material purposes, such as landscaping [11]. Urban foraging (also called 'urban gathering' or 'urban collecting') can occur in a wide variety of spaces, both managed and unmanaged, public and Sustainability 2018, 10, 1873 2 of 23 private, including parks and forests, abandoned lots, alongside streets and in nature preserves [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…This raises a number of social justice questions, namely who has access to the natural resources in the city? According to Poe et al [54], "An urban forest justice framework…recognizes the rights of urban people to control their own culturally appropriate food and health systems based in cultures of gathering wild edible and medicinal plants and fungi". A particular form of urban foraging is called "dumpster diving" It is a popular form of modern salvaging of waste discarded in large commercial, residential, industrial and construction containers.…”
Section: Urban Foraging and Ecologymentioning
confidence: 99%
“…In addition, foraging is an activity which can build community and intergenerational bonds, inspire exercise, serve as a supplemental source of income, and offer a way for people to connect to nature [54]. In other words, urban foraging is underpinned by interconnected and multiple notions of identity, place, mobility, and agency for both humans and more-than-human interlocutors [55].…”
Section: Urban Foraging and Ecologymentioning
confidence: 99%
See 1 more Smart Citation